IMPLEMENTASI KEBIJAKAN TENTANG PEDOMAN PERIZINAN USAHA PERKEBUNAN DI KABUPATEN MAHAKAM ULU - Kueng, Ding; Kusuma, Aji Ratna; Paselle, Enos (Jurnal Administrative Reform, 2024)
This research aims to analyze the implementation of the Minister of Agriculture's Regulation concerning Guidelines for Plantation Business Licensing in Mahakam Ulu Regency and the inhibiting factors. The research uses descriptive qualitative research with data types including primary data and secondary data through interactive model analysis. The research results show that the communication aspect of policy implementation as the executor of plantation business licensing services is not optimal even though coordination has been carried out with relevant stakeholders but there has been no socialization since the transfer of licensing from West Kutai Regency to Mahakam Ulu Regency. In the aspect of human resources, they are not adequate in quality or quantity and equipment resources are also inadequate to support policy implementation. In the disposition aspect, plantation business permits have a commitment to implementing policy procedures well and receiving support from stakeholders. In terms of the organizational structure aspect, the policy guidelines for plantation business permit services in Mahakam Ulu Regency have a fairly adequate organizational structure between implementers, both from DKPP and the Department of Investment and Integrated Licensing Services (DPMPPT). Then, the factor that hampers the implementation of the Minister of Agriculture's Regulation regarding guidelines for plantation business licensing in Mahakam Ulu Regency is the unavailability of a special budget for plantation business licensing at the Mahakam Ulu Regency Food Security and Agriculture Service.